Advancing Foundry Training Through Virtual Reality: A Low-Cost, Immersive Learning Environment - Anson Fry; Ismail Fidan; Eric Wooldridge (Inventions)
Metal casting foundries present hazardous working conditions, making traditional training methods costly, time-consuming, and potentially unsafe. To address these challenges, this study presents a Virtual Reality (VR) training framework developed for the Tennessee Tech University (TTU) Foundry. The objective is to enhance introductory training and safety education by providing an immersive, interactive, and risk-free environment where trainees can familiarize themselves with safety protocols, equipment handling, process workflows, and machine arrangements before engaging with real-world operations. The VR foundry environment is designed using Unreal Engine, a freely available software tool, to create a high-fidelity, interactive simulation of metal casting processes. This system enables real-time user interaction, scenario-based training, and procedural guidance, ensuring an engaging and effective learning experience. Preliminary findings and prior research indicate that VR-based training enhances learning retention, improves hazard recognition, and reduces training time compared to traditional methods. While challenges such as haptic feedback limitations and initial setup costs exist, VR’s potential in engineering education and industrial training is substantial. This work-in-progress study highlights the transformative role of VR in foundry training, contributing to the development of a safer, more efficient, and scalable workforce in the metal casting industry.